Carbon ceramic composite friction material and preparation method thereof

Through the specific ratio and process of carbon ceramic composite friction materials, the problems of easy oxidation and poor high-temperature resistance of carbon ceramic composite friction materials in high-temperature environments are solved, and high-temperature oxidation stability, friction coefficient stability and wear resistance are achieved. It reduces braking noise and production costs, and is suitable for large-scale production.

CN119122959APending Publication Date: 2024-12-13ZHEJIANG TAIJI FRICTION MATERIAL CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411262623.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Carbon ceramic composite friction materials are prone to oxidation in high temperature environments and have poor high temperature resistance, resulting in increased braking noise and unstable friction coefficient, and high production costs, making it difficult to achieve large-scale production.

Method used

The raw materials such as chopped carbon fiber, ceramic fiber, calcium sulfate whiskers, micropore fillers, friction-increasing regulators, friction-reducing regulators, ultrafine silicon carbide and polysilazane are used to form a raw material such as special ratios and processes. High-temperature resistant carbon ceramic composite friction material reduces the use of phenolic resin, avoids long-term high-temperature sintering, and uses polytetrafluoroethylene powder to improve molding effect.

Benefits of technology

It realizes the high-temperature oxidation stability, friction coefficient stability and wear resistance of carbon ceramic composite friction materials, reduces braking noise, reduces production costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119122959A_ABST
    Figure CN119122959A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon ceramic composite friction material and a preparation method thereof. The carbon ceramic composite friction material is prepared from the following raw materials in parts by weight: 5-10 parts of short carbon fibers, 15-25 parts of ceramic fibers, 15-25 parts of calcium sulfate whiskers, 10-15 parts of microporous filler, 3-5 parts of a friction increasing regulator, 3-5 parts of a friction reducing regulator, 0.2-0.5 part of superfine silicon carbide, 0.05-0.1 part of a dispersing agent, 3-6 parts of polysilazane and 3-5 parts of high-temperature-resistant phenolic resin. And 0.5-1 part of polytetrafluoroethylene powder. Polysilazane is adopted to treat short carbon fibers, so that the carbon fibers form a good ceramic high-temperature-resistant layer, and high-temperature oxidation of the carbon fibers in the carbon-ceramic composite friction material is effectively prevented; the use amount of phenolic resin is reduced, and the high-temperature stability of the carbon-ceramic composite friction material is improved. Through cooperation of the friction-increasing modifier, the friction-reducing modifier, the calcium sulfate whiskers, the microporous filler and the polytetrafluoroethylene, the friction coefficient is kept stable at high temperature during braking, and abrasion caused during high-load braking is reduced. Long-time high-temperature sintering is not needed in the production process, and energy-saving and environment-friendly preparation of the carbon-ceramic friction material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of special friction materials and relates to a carbon ceramic composite friction material and a preparation method thereof. Background Art

[0002] Friction materials are functional materials used in various braking and transmission applications due to their wear resistance and friction properties. For example, in the field of braking, friction materials are made into brake pads for automobile brake pads, motorcycle brake pads, industrial automatic control brake pads, wind power brake pads, high-speed rail brake pads, etc.; in the field of transmission, friction materials are used for clutch friction pads, etc. The performance of friction materials directly affects the stability of the machine and the safety of passengers. According to different materials, friction materials have been formed into asbestos friction materials, semi-metal friction materials, powder metallurgy friction materials, ceramic fiber friction materials, carbon fiber friction materials, etc.

[0003] The friction coefficient stability, wear resistance, rusting, brake noise, damage to the dual disc, heat dissipation and other properties of friction materials seriously affect the use of friction materials. With the technological updates of new energy vehicles, aerospace technology, machinery manufacturing, wind power, etc., the requirements for friction materials are getting higher and higher. Asbestos friction materials produce asbestos fiber fine powder due to brake friction, which will affect human health. From the perspective of environmental protection, asbestos friction materials are gradually eliminated; semi-metallic friction materials have excellent wear resistance, but the high metal content makes the braking force insufficient at low temperatures, and the high heating rate causes heat to be transferred to the brake caliper and its components, which will accelerate the aging of components such as the brake caliper, and easily cause the brake lining to peel or crack; powder metallurgy friction materials have a large friction coefficient, can remain stable in a wide temperature range, and have high strength, allowing the use of high-load pressure brakes. They are currently widely used in high-speed rail and wind power, but powder metallurgy friction materials require a higher sintering temperature, which will cause the metal grains to grow, affecting the performance of the material, and powder metallurgy friction materials have high thermal conductivity and thermal expansion heat during high-frequency braking, which is easy to crack.

[0004] Ceramic-based friction materials have stable friction coefficients at high and low temperatures, low wear rates, long life, less wear dust, and can withstand greater pressure and shear force. In high-strength brake pads, friction materials are required to have good thermal stability of friction coefficients, low wear rates, and less dust. Therefore, ceramic-based friction materials have begun to be used in brake pads for heavy trucks, high-speed railways, wind power, and aircraft. In particular, carbon-ceramic composite friction materials combine the advantages of carbon / carbon composite materials and ceramic-based composite materials, and have the characteristics of low density, high temperature resistance, and long life. They have great application prospects in high-load, lightweight high-speed trains, wind power, new energy vehicles, heavy trucks, aircraft, ships, etc.

[0005] However, carbon-ceramic composite friction materials encounter many technical problems during production and use, resulting in high manufacturing costs and technical bottlenecks in stable large-scale production. This is mainly reflected in:

[0006] First of all, the high-temperature oxidation resistance of carbon fiber materials is poor. Generally, when the temperature reaches above 400°C in an air environment, weight loss and strength reduction will occur. When it exceeds 500°C, it will quickly oxidize and decompose, thereby losing the performance of the composite material and causing structural damage. Therefore, when carbon fiber is used to reinforce ceramic friction materials, it needs to be treated with antioxidant protection. The technology is not easy to control and the operation is difficult. Chinese invention patent publication number CN105601344 B discloses a medium-temperature antioxidant coating, a preparation method thereof, and a carbon / carbon composite material product, which adopts the method of coating an antioxidant coating on a carbon / carbon material product to prevent high-temperature oxidation of carbon. However, when used as a friction material, as the antioxidant coating on the surface of the product wears, the high-temperature oxidation resistance of the carbon material will decay.

[0007] Furthermore, at present, most carbon ceramic friction materials are formed by phenolic resin bonding and thermal curing, and their high temperature resistance is poor. Carbon ceramic-based friction materials use carbon fiber and ceramic fiber as the main raw materials, and are processed by precursor impregnation cracking method, reaction infiltration method, etc., which require high-temperature sintering and carbonization treatment under protective gas conditions, resulting in high costs and high energy consumption in production conditions. Generally speaking, the normal braking temperature range is 150-300℃, and the instantaneous high-speed braking temperature can reach 400℃, while the phenolic resin adhesive of the friction material decomposes at 300℃.

[0008] In addition, the current carbon-ceramic composite friction material is hard and brittle, and it is easy to produce brake squeal noise when used for braking. At the same time, the instantaneous high temperature generated by braking will cause the carbon material to oxidize, resulting in increased wear and a decrease in braking performance. Summary of the invention

[0009] In view of the defects of the current carbon ceramic composite friction material, such as poor high temperature resistance of the adhesive resin, easy high temperature oxidation loss of carbon materials, and easy generation of brake squealing noise, the present invention proposes a carbon ceramic composite friction material, which has good high temperature oxidation resistance, stable high temperature friction coefficient, and both hard and tough properties, thus overcoming the defect of easy generation of brake squealing noise. At the same time, a preparation method of the carbon ceramic composite friction material is proposed, which does not require long-term high temperature sintering, and realizes energy-saving and environmentally friendly preparation of carbon ceramic friction materials.

[0010] In order to achieve the above technical objectives, the following technical solutions are adopted:

[0011] The first technical purpose is to propose a carbon ceramic composite friction material, characterized in that the raw materials used to prepare the carbon ceramic composite friction material are calculated by weight: 5-10 parts of chopped carbon fiber, 15-25 parts of ceramic fiber, 15-25 parts of calcium sulfate whisker, 10-15 parts of microporous filler, 3-5 parts of friction modifier, 3-5 parts of friction modifier, 0.2-0.5 parts of ultrafine silicon carbide, 0.05-0.1 parts of dispersant, 3-6 parts of polysilazane, 3-5 parts of high temperature resistant phenolic resin; 0.5-1 parts of polytetrafluoroethylene powder; wherein,

[0012] The friction modifier is selected from at least one of white carbon black, sepiolite, brucite and wollastonite;

[0013] The friction reducing agent is selected from at least one of molybdenum disulfide, tungsten disulfide, bismuth trioxide, flake graphite, and mica powder.

[0014] Preferably, the single filament diameter of the chopped carbon fiber is 7-15 μm, and the filament length is 5-10 mm.

[0015] Preferably, the ceramic fiber is selected from at least one of high-aluminum aluminum silicate fiber, polycrystalline alumina fiber, polycrystalline mullite fiber, silicon carbide fiber, silicon nitride fiber, zirconium dioxide fiber, and silicon carbon nitrogen fiber with a diameter of 5-15 μm and a length of 5-10 mm.

[0016] Preferably, the calcium sulfate whiskers are fine calcium sulfate whiskers with a diameter of 5-10 μm and a length of 100-400 μm; fine calcium sulfate whiskers have the characteristics of high strength, high modulus, high toughness and wear resistance. By using a large amount of calcium sulfate whiskers, not only the strength and wear resistance of the friction material are increased, but also the cost is reduced, the flexibility of the friction material is increased, thereby reducing brake squeal noise.

[0017] Preferably, the microporous filler is at least one of expanded vermiculite, zeolite powder and diatomaceous earth; the microporous filler has fine pores, which can be used for the friction material to quickly absorb the gaseous substances released by the thermal decomposition of the resin and the heat generated by friction when the brake is at high temperature, and at the same time help reduce the howling noise.

[0018] The friction-increasing modifier has good stickiness and friction-increasing properties; the friction-reducing modifier has good lubrication properties. During high-load braking, its lubrication properties can effectively prevent brake locking and reduce wear caused during high-load braking.

[0019] Conventional friction materials, as the brake temperature increases, the friction coefficient usually decays rapidly, and continuous braking often causes brake failure, mainly due to the instability of the friction coefficient of the friction material at high temperatures. Through the reasonable combination of friction modifiers and friction modifiers, the friction coefficient of the friction material can be adjusted to a reasonable range. In addition, the friction coefficient of the friction material is kept stable when the brake temperature is high.

[0020] Preferably, the particle size of the ultrafine silicon carbide is less than 5 μm. Silicon carbide has excellent wear resistance. The ultrafine silicon carbide can be fully dispersed by auxiliary use of a dispersant, which can increase the wear-resistant interface in the friction material.

[0021] Preferably, the dispersant is selected from at least one of sodium dodecylbenzene sulfonate, polyvinyl alcohol, sodium hexametaphosphate, sodium pyrophosphate, and sodium polyacrylate; by using the dispersant, the friction modifier, the friction modifier, the ultrafine silicon carbide and the fibrous material can be fully dispersed to prevent agglomeration. In particular, the efficient dispersion of ultrafine silicon carbide will increase its dispersibility in the friction material and increase the wear-resistant interface, which is positive for improving the wear-resistant effect.

[0022] Preferably, the polysilazane is selected from one of low-viscosity perhydropolysilazane, methylpolysilazane and vinylpolysilazane with a viscosity of 10-50cp. Polysilazane is a liquid polymer with Si-N bonds as repeating units in the main chain, which is easy to apply and is used for pre-coating chopped carbon fibers. It is cured, bonded and ceramicized at high temperatures to form a high-temperature resistant layer at the interface of the carbon fibers to prevent high-temperature oxidation losses of the carbon fibers. At the same time, the use of polysilazane can make the carbon fibers firmly bonded to other materials to form friction materials, reduce the use of phenolic resin adhesives, and improve high-temperature friction stability.

[0023] Furthermore, as a preference, the polysilazane is selected from perhydropolysilazane, which can be quickly bonded and cured at 300-400°C to form a ceramic coating, thus avoiding long-term high-temperature sintering and greatly saving production energy consumption; when using organic polysilazane (methyl polysilazane, vinyl polysilazane), a high temperature of 450-500°C is used to generate a ceramic coating in situ, which is effective in preventing high-temperature oxidation loss of carbon fiber.

[0024] Preferably, the high temperature resistant phenolic resin is selected from at least one of boron-doped modified phenolic resin, molybdenum-doped modified phenolic resin and benzoxazine modified phenolic resin.

[0025] Preferably, the polytetrafluoroethylene is selected to be fine particles with a particle size of less than 10um; on the one hand, polytetrafluoroethylene has adhesion when the friction material is hot-pressed, which can improve the molding effect of the friction material; on the other hand, polytetrafluoroethylene is easy to form a lubricating film during friction, which reduces friction and improves the wear resistance of the friction material; a more excellent effect is that polytetrafluoroethylene has a lower surface free energy and is not easy to adhere to debris. When the friction material is working, it prevents the powder, external impurities, oil stains, etc. generated by friction from adhering to the brake pad, always keeping the interface of the friction material clean, thereby making the friction coefficient of the friction material interface more stable.

[0026] The second technical purpose is to provide a method for preparing a carbon ceramic composite friction material, which is characterized in that the specific preparation method is as follows:

[0027] (1) pre-baking the chopped carbon fiber at 120° C. for more than 2 hours, adding the chopped carbon fiber into a three-dimensional mixer according to the weight ratio, breaking up the stranded chopped carbon fiber by stirring, and then adding polysilazane and stirring evenly to make the polysilazane fully adhere to the surface of the chopped carbon fiber; and storing it in a sealed manner as material A;

[0028] (2) adding calcium sulfate whiskers, microporous fillers, friction modifiers, friction modifiers, ultrafine silicon carbide, dispersants, and polytetrafluoroethylene powder into a high-speed mixer according to weight ratio, mixing evenly, and then adding high temperature resistant phenolic resin and stirring evenly, and storing as material B;

[0029] (3) Mix the ceramic fiber, material A and material B in a V-type mixer, weigh them automatically according to the amount of friction material, add them into the mold, the mold temperature is 100-200°C, the pre-pressing pressure is 1-2MPa, and the holding time is 10s; then pressurize to 30-35MPa, and the holding time is 1-2min;

[0030] (4) After demolding, the material is heat treated in a high temperature furnace for 10-15 minutes, and then polished and trimmed to obtain a carbon ceramic composite friction material.

[0031] In step (1), the chopped carbon fibers need to be fully dried. Polysilazane is easily hydrolyzed and unstable. The chopped carbon fibers adhering to polysilazane are stored in a sealed storage tank; preferably, they are used up within 6 hours.

[0032] The rotation speed of the three-dimensional mixer in step (1) is a low speed of 5-10 rpm. The three-dimensional motion mixing makes the short-cut carbon fibers free from centrifugal force, gravity segregation and stratification, and prevents the fibers from entanglement and agglomeration.

[0033] Preferably, the mold in step (3) is replaced according to the shape requirements of the brake pad, clutch plate, brake shoe, and brake band; further, the steel back can be pre-placed in the mold for integrated molding as needed, and the friction material can be directly pressed onto the steel back.

[0034] When the polysilazane used is perhydropolysilazane, the high temperature heat treatment temperature of step (4) is controlled at 300-400°C; when an organic polysilazane (methyl polysilazane, vinyl polysilazane) is used, the high temperature heat treatment temperature of step (4) is controlled at 450-500°C.

[0035] Preferably, during the heat treatment in step (4), the high temperature furnace is evacuated or protected with nitrogen, which can better prevent oxidation loss of the carbon fiber during the heat treatment.

[0036] Compared with the prior art, the present invention has the following positive and beneficial effects:

[0037] 1. The present invention uses polysilazane to treat chopped carbon fibers, so that the carbon fibers form a good ceramic high-temperature resistant layer, which effectively prevents high-temperature oxidation of the carbon fibers in the carbon-ceramic composite friction material; moreover, the good porcelain bonding property of polysilazane can reduce the amount of phenolic resin used and improve the high-temperature stability of the carbon-ceramic composite friction material.

[0038] 2. The friction-increasing modifier selected in the present invention has good stickiness and friction-increasing properties, and the friction-reducing modifier has good lubrication properties; through the reasonable combination of the friction-increasing modifier and the friction-reducing modifier, the friction coefficient of the friction material can be adjusted to a reasonable range. The friction coefficient of the friction material is kept stable when the brake is at high temperature, and its lubrication properties can effectively prevent the brake from locking during high-load braking, reducing the wear caused by high-load braking.

[0039] 3. The present invention uses more calcium sulfate whiskers to increase the strength and wear resistance of the friction material, reduce costs, increase the flexibility of the friction material, and thus reduce brake squealing noise. The use of microporous fillers can quickly absorb the gaseous substances released by the thermal decomposition of the resin and the heat generated by friction, while helping to reduce the squealing noise.

[0040] 4. The present invention uses polytetrafluoroethylene, which has adhesiveness when the friction material is hot-pressed and can improve the molding effect of the friction material. Polytetrafluoroethylene forms a lubricating film during friction to improve the wear resistance of the friction material. Since polytetrafluoroethylene has a lower surface free energy and is not easy to adhere to debris, it prevents the adhesion of powder, foreign impurities, oil stains, etc. generated by friction when the friction material is working, and always keeps the interface of the friction material clean, thereby making the friction coefficient of the interface of the friction material more stable.

[0041] 5. The technical solution of the present invention has low cost for preparing carbon ceramic composite friction materials, and the preparation process is easy to control, which is suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly and directly understand the preparation technology process of the present invention, the present invention is further described below in conjunction with the accompanying drawings:

[0043] Figure 1 The present invention is a process flow chart for preparing carbon ceramic composite friction material. DETAILED DESCRIPTION

[0044] In order to enable those skilled in the art to better understand the solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the technical ideas of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0045] Some raw materials involved in the implementation of the plan:

[0046] Calcium sulfate whiskers: brand DL-10, diameter 5-10μm, length 50-200μm, produced by Changzhou Guangwei New Material Technology Co., Ltd.

[0047] Chopped carbon fiber: fiber diameter 7μm, produced by Changzhou Yaobang Friction Material Factory.

[0048] Silicon carbide: 3000 mesh, produced by Shandong Jinmeng New Materials Co., Ltd.

[0049] Example 1

[0050] A method for preparing a carbon ceramic composite friction material, the specific preparation method is as follows:

[0051] (1) Pre-dry the chopped carbon fibers at 120° C. for more than 2 hours, add 10 parts of the chopped carbon fibers into a three-dimensional mixer according to the weight ratio, stir at a low speed of 10 rpm to break up the strands of chopped carbon fibers, then add 6 parts of perhydropolysilazane with a viscosity of 25 cp and stir evenly to allow the polysilazane to fully adhere to the surface of the chopped carbon fibers; and store them in a sealed manner as material A;

[0052] (2) According to the weight ratio, 20 parts of calcium sulfate whiskers, 10 parts of microporous filler expanded vermiculite, 3 parts of friction modifier white carbon black, 4 parts of friction modifier bismuth trioxide, 0.5 parts of ultrafine silicon carbide, 0.05 parts of dispersant sodium hexametaphosphate, and 0.5 parts of polytetrafluoroethylene powder with a particle size of less than 10 μm were added to a high-speed mixer and mixed at a speed of 400 rpm for 20 minutes, and then 4 parts of benzoxazine-modified phenolic resin were added and stirred evenly, and stored as material B;

[0053] (3) 10 parts of ceramic fiber high aluminum silicate fiber with a diameter of 5-15 μm and a length of 5-10 mm, 5 parts of polycrystalline alumina fiber, 5 parts of silicon carbide fiber, material A and material B are mixed in a V-type mixer, automatically weighed according to the amount of friction material, added to the mold, the mold temperature is 200°C, the pre-pressing pressure is 1 MPa, and the holding time is 10 s; then the pressure is increased to 30 MPa, and the holding time is 2 min;

[0054] (4) After demolding, the material is heat treated in a high-temperature furnace at 400° C. under vacuum conditions for 15 min, and then polished and trimmed to obtain a carbon-ceramic composite friction material.

[0055] Example 2

[0056] A method for preparing a carbon ceramic composite friction material, the specific preparation method is as follows:

[0057] (1) pre-baking the chopped carbon fiber at 120° C. for more than 2 hours, adding 8 parts of the chopped carbon fiber into a three-dimensional mixer according to the weight ratio, stirring at a low speed of 10 rpm to break up the stranded chopped carbon fiber, and then adding 5 parts of perhydropolysilazane with a viscosity of 25 cp and stirring evenly to make the polysilazane fully adhere to the surface of the chopped carbon fiber; and storing it in a sealed manner as material A;

[0058] (2) According to the weight ratio, 25 parts of calcium sulfate whiskers, 12 parts of microporous filler diatomaceous earth, 4 parts of friction modifier wollastonite, 5 parts of friction modifier tungsten disulfide, 0.4 parts of ultrafine silicon carbide, 0.05 parts of dispersant polyvinyl alcohol, and 0.8 parts of polytetrafluoroethylene powder with a particle size of less than 10 μm were added into a high-speed mixer and mixed at a speed of 400 rpm for 20 minutes, and then 5 parts of boron-doped modified phenolic resin were added and stirred evenly, and stored as material B;

[0059] (3) 10 parts of ceramic fiber high aluminum silicate fiber with a diameter of 5-15 μm and a length of 5-10 mm, 10 parts of polycrystalline mullite fiber, 3 parts of silicon carbide fiber, material A and material B are mixed in a V-type mixer, automatically weighed according to the amount of friction material, added to the mold, the mold temperature is 200°C, the pre-pressing pressure is 1 MPa, and the holding time is 10 s; then the pressure is increased to 35 MPa, and the holding time is 2 min;

[0060] (4) After demolding, the material is heat treated in a high-temperature furnace at 400° C. under vacuum conditions for 15 min, and then polished and trimmed to obtain a carbon-ceramic composite friction material.

[0061] Example 3

[0062] A method for preparing a carbon ceramic composite friction material, the specific preparation method is as follows:

[0063] (1) pre-baking the chopped carbon fiber at 120° C. for more than 2 hours, adding 10 parts of the chopped carbon fiber into a three-dimensional mixer according to the weight ratio, stirring at a low speed of 8 rpm to break up the stranded chopped carbon fiber, and then adding 4 parts of methyl polysilazane with a viscosity of 10 cp and stirring evenly to make the polysilazane fully adhere to the surface of the chopped carbon fiber; and storing it in a sealed manner as material A;

[0064] (2) According to the weight ratio, 20 parts of calcium sulfate whiskers, 10 parts of microporous filler zeolite powder, 3 parts of friction modifier sepiolite, 5 parts of friction modifier molybdenum disulfide, 0.5 parts of ultrafine silicon carbide, 0.05 parts of dispersant sodium pyrophosphate, and 1 part of polytetrafluoroethylene powder with a particle size of less than 10 μm were added into a high-speed mixer and mixed at a speed of 400 rpm for 20 minutes, and then 4 parts of molybdenum-doped modified phenolic resin were added and stirred evenly, and stored as material B;

[0065] (3) 10 parts of ceramic fiber high aluminum silicate fiber with a diameter of 5-15 μm and a length of 5-10 mm, 10 parts of polycrystalline alumina fiber, 1 part of silicon nitride fiber, material A and material B are mixed in a V-type mixer, automatically weighed according to the amount of friction material, added to the mold, the mold temperature is 200°C, the pre-pressing pressure is 1 MPa, and the holding time is 10 s; then the pressure is increased to 30 MPa, and the holding time is 2 min;

[0066] (4) After demolding, the material is heat treated in a high-temperature furnace at 500° C. under vacuum conditions for 15 min, and then polished and trimmed to obtain a carbon-ceramic composite friction material.

[0067] Comparative Example 1

[0068] According to the scheme of Example 1, the perhydropolysilazane was replaced with benzoxazine-modified phenolic resin. The phenolic resin ensures good bonding of the materials, but since a ceramic layer cannot be formed at the carbon fiber interface, the obtained friction material has oxidation loss during high-temperature braking, which is manifested as high wear under high-temperature conditions and unstable high-temperature friction coefficient.

[0069] Comparative Example 2

[0070] According to the scheme of Example 1, 4 parts of the friction reducing agent bismuth trioxide were replaced by white carbon black. Although the friction coefficient was improved, the friction coefficient stability of the friction material was poor at high braking temperature due to the lack of friction reducing agent.

[0071] Comparative Example 3

[0072] According to the scheme of Example 1, 20 parts of calcium sulfate whiskers are reduced to 5 parts of calcium sulfate whiskers, and 15 parts of calcium carbonate powder are added. A higher amount of calcium sulfate whiskers not only reduces costs, but also improves the wear resistance of the friction material and the stability of the friction coefficient, while increasing the flexibility of the friction material, thereby reducing brake squeal noise. When the amount of calcium sulfate whiskers is reduced, not only the stability of the friction coefficient is affected, but also the brake squeal is significantly increased.

[0073] Comparative Example 4

[0074] According to the scheme of Example 1, 0.5 parts of polytetrafluoroethylene powder is eliminated. Using polytetrafluoroethylene can easily form a lubricating film during friction, thereby improving the wear resistance of the friction material; eliminating polytetrafluoroethylene will cause the powder and oil generated during the operation of the friction material to easily adhere, resulting in an unstable friction coefficient.

[0075] Comparative Example 5

[0076] According to the scheme of Example 1, 10 parts of microporous filler expanded vermiculite were replaced with an equal amount of calcium carbonate. The use of microporous filler can quickly absorb the gaseous substances released by the thermal decomposition of the resin and the heat generated by friction, while reducing the whistling noise. The removal of microporous filler has a greater impact on the high-temperature friction performance, and the whistling noise is obvious.

[0077] Friction material performance evaluation:

[0078] The room temperature friction coefficient and high temperature friction coefficient of each test friction material sample were tested with reference to GB / T 17469-2012 “Small sample bench test method for evaluating the friction performance of automobile brake linings”, as shown in Table 1.

[0079] The volume wear rate of each test friction material sample under different temperature conditions was tested with reference to GB5763-2018 “Test methods for brake linings for automobiles”, as shown in Table 1.

[0080] Table 1:

[0081] Through testing, the synergistic combination of the raw materials of the present invention has resulted in a friction material with excellent high temperature resistance, low attenuation of the high temperature friction coefficient, stable friction coefficient, wear resistance, little damage to the mating parts, and low friction whistling noise. This carbon-ceramic composite friction material has both the flexibility and strength of carbon fiber and the high modulus and hardness of ceramics, as carbon fiber is used as a reinforcement, and has significant advantages in the fields of wind power brakes, aircraft brakes, high-speed rail brakes, and new energy vehicle brakes.

[0082] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A carbon ceramic composite friction material, Its characteristics are The raw materials used to prepare the carbon ceramic composite friction material are calculated by weight: 5-10 parts of chopped carbon fiber, 15-25 parts of ceramic fiber, 15-25 parts of calcium sulfate whisker, 10-15 parts of microporous filler, 3-5 parts of friction modifier, 3-5 parts of friction modifier, 0.2-0.5 parts of ultrafine silicon carbide, 0.05-0.1 parts of dispersant, 3-6 parts of polysilazane, 3-5 parts of high temperature resistant phenolic resin; 0.5-1 parts of polytetrafluoroethylene powder; wherein, The friction modifier is selected from at least one of white carbon black, sepiolite, brucite and wollastonite; The friction reducing agent is selected from at least one of molybdenum disulfide, tungsten disulfide, bismuth trioxide, flake graphite, and mica powder.

2. A carbon ceramic composite friction material according to claim 1, Its characteristics are: The single filament diameter of the chopped carbon fiber is 7-15 μm, and the length of the filament is 5-10 mm; the ceramic fiber is selected from at least one of high-aluminum aluminum silicate fiber, polycrystalline alumina fiber, polycrystalline mullite fiber, silicon carbide fiber, silicon nitride fiber, zirconium dioxide fiber, and silicon carbon nitrogen fiber with a diameter of 5-15 μm and a length of 5-10 mm; the calcium sulfate whisker is selected from fine calcium sulfate whiskers with a diameter of 5-10 μm and a length of 100-400 μm.

3. The carbon ceramic composite friction material according to claim 1, Its characteristics are: The microporous filler is selected from at least one of expanded vermiculite, zeolite powder and diatomaceous earth.

4. The carbon ceramic composite friction material according to claim 1, Its characteristics are: The particle size of the ultrafine silicon carbide is less than 5 um.

5. The carbon ceramic composite friction material according to claim 1, Its characteristics are: The dispersant is selected from at least one of sodium dodecylbenzene sulfonate, polyvinyl alcohol, sodium hexametaphosphate, sodium pyrophosphate and sodium polyacrylate.

6. The carbon ceramic composite friction material according to claim 1, Its characteristics are: The polysilazane is selected from one of low-viscosity perhydropolysilazane, methylpolysilazane and vinylpolysilazane having a viscosity of 10-50 cp.

7. The carbon ceramic composite friction material according to claim 1, Its characteristics are: The high temperature resistant phenolic resin is selected from at least one of boron doped modified phenolic resin, molybdenum doped modified phenolic resin and benzoxazine modified phenolic resin.

8. The carbon ceramic composite friction material according to claim 1, Its characteristics are: The polytetrafluoroethylene is selected as fine particles with a particle size less than 10 um.

9. A method for preparing a carbon ceramic composite friction material according to any one of claims 1 to 8, Features: The specific preparation method is as follows: (1) pre-baking the chopped carbon fiber at 120° C. for more than 2 hours, adding the chopped carbon fiber into a three-dimensional mixer according to the weight ratio, breaking up the stranded chopped carbon fiber by stirring, and then adding polysilazane and stirring evenly to make the polysilazane fully adhere to the surface of the chopped carbon fiber; and storing it in a sealed manner as material A; (2) adding calcium sulfate whiskers, microporous fillers, friction modifiers, friction modifiers, ultrafine silicon carbide, dispersants, and polytetrafluoroethylene powder into a high-speed mixer according to weight ratio, mixing evenly, and then adding high temperature resistant phenolic resin and stirring evenly, and storing as material B; (3) Mix the ceramic fiber, material A and material B in a V-type mixer, weigh them automatically according to the amount of friction material, add them into the mold, the mold temperature is 100-200°C, the pre-pressing pressure is 1-2MPa, and the holding time is 10s; then pressurize to 30-35MPa, and the holding time is 1-2min; (4) After demolding, the material is heat treated in a high temperature furnace for 10-15 minutes, and then polished and trimmed to obtain a carbon ceramic composite friction material.

10. A method for preparing a carbon ceramic composite friction material according to claim 9, Features: When the polysilazane used is perhydropolysilazane, the high temperature heat treatment in step (4) is controlled at 300-400°C; when an organic polysilazane is used, the high temperature heat treatment in step (4) is controlled at 450-500°C.

Citation Information

Cited By

  • Copper-based wear-resistant clutch friction plate and preparation process thereof

    CN119932362A

  • A copper-based wear-resistant clutch plate and a preparation process thereof

    CN119932362B

  • High-temperature-resistant resin composition, friction material using composition as adhesive and preparation method of friction material

    CN122563271A